Initial degree of detaching bubble adsorption coverage and the kinetics of dynamic adsorption layer formation. Issue 4 (8th January 2018) - Kosior, Dominik; Zawala, Jan
Abstract : We show, for the first time, the influence of the initial adsorption coverage over a bubble on the kinetics of dynamic adsorption layer formation. Abstract : The influence of the initial adsorption coverage at the surface of an air bubble (radius 0.74 mm) formed at a capillary orifice on profiles of its rising velocities and shape variations was investigated in n -octanol, n -octyltrimethylammonium bromide (CTAB) and Tween80 solutions of different concentrations. The bubble formation and the degree of adsorption coverage at its surface at the moment of departure were controlled using an elaborated automatic bubble generator (Bubble-on-Demand) coupled with a programmable bubble trap, allowing adsorption time control over the motionless (captured) bubble interface. It was found that the degree of the initial bubble adsorption coverage (whose value was calculated according to the existing adsorption models), has a profound influence on the kinetics of the dynamic adsorption layer (DAL) development.